Equality & excellence in ancient and modern political philosophy - Frankel, Steven, 1968-; Ray, John A., 1957- ([ALbany] : State University of New York Press, 2023)
Interpretations of critically important texts in political philosophy from Greek antiquity to modern times on the tension between human excellence and equality and its possible resolution.
Pursuing the Forms: Equality and Excellence in Plato's Republic and Symposium -- Equality and Excellence in the Education of Cyrus -- Splendid Equality in the Nicomachean Ethics: Munificence -- How Excellence Bows to Equality in Aristotle's Politics -- First Among Equals: Philosophers, Statesmen, and Citizens in Spinoza's Democracy -- Excellence and Equality in Fénelon's Telemachus -- The Seductive Danger of Equality and Excellence: The Moderating Wisdom of Montesquieu's Science of Ovidian Metamorphosis -- Equality and Excellence in Rousseau's Emile, Book III -- Hegel's Evaluation of Liberalism: Equality of Rights without Human Excellence -- Democracy, Nobility, and Freedom: The Political and Moral Aesthetics of Tocqueville -- Does Kierkegaard Have a Concept of Excellence? -- Nietzsche: The Indignity of Equality -- The Good and the Excellent: John Rawls's Egalitarian Liberalism.
Description based upon print version of record.
Includes bibliographical references and index
eBooks on EBSCOhost
Keywords: Political science -- Philosophy -- History; Equality -- Political aspects; Excellence; Excellence; POLITICAL SCIENCE / History & Theory; Excellence; Political science -- Philosophy; Political science; Electronic books; History